Modeling approaches for hepatic spatial heterogeneity in pharmacokinetic simulations. (2016) - Schwen, Lars Ole; Kuepfer, Lars; Preusser, Tobias
Abstract : The metabolization and excretion of drugs in the liver are spatially heterogeneous processes. This is due to the spatial variability of physiological processes at different length scales of biological organization in healthy individuals, while many liver diseases further contribute to the heterogeneity. Classical, well-stirred pharmacokinetic models do not represent this heterogeneity, and various modeling approaches capable of representing heterogeneity have been developed recently. These approaches range from mechanistic and physio-geometrically realistic models focusing on specific spatial scales, via continuum models using homogenized physiological and metabolic properties, to integrative multiscale models. Such models could become essential research tools for simulations involving drugs with notable first-pass effects, fast-acting drugs or tracers, and diseased livers.